Корабль-призрак: [роман] / Фредерик Марриет - Марриэт Фредерик (Классика жанра, 2013)
Экземпляры: аб. ЦБ (2017.02.05) / Инвентарный номер: 3041 / Цена: 110.00 / Сис.шифр: 84(4Вел) / Авт.знак: М 25 / ГРНТИ: 17.82 / ББК: 84(4Вел)